The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1037/0021-9010.69.2.349
|View full text |Cite
|
Sign up to set email alerts
|

Sex bias and managerial evaluations: A replication and extension.

Abstract: The present investigation replicates and extends the recent work of both Mobley (1982) and Wexley and Pulakos (1982) on sex bias in performance appraisals. The study focuses on supervisory ratings of managers working on the same job m the same organization Furthermore, the rating scales used were specifically developed to reflect the content of that managerial job. Results from this investigation indicated a significant main effect for ratee sex, favoring females over males, and nonsignificant effects for rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…This ®nding was somewhat unexpected, as it indicated signi®cantly higher Overall Performance for the women in all but the skewed units. Evidence of a pro-female bias in situations where (based on stereotypical assumptions) a pro-male bias was anticipated is occasionally found both in laboratory (Bigoness, 1976;Hamner et al, 1974;Jacobson and Effertz, 1974;Kryger and Shikiar, 1978;Pazy, 1992;Woehr and Roch, 1996) and in ®eld studies (Mobley, 1982;Peters et al, 1984;Powell and Butter®eld, 1994). The tendency to in¯ateÐrather than devalueÐthe assessment of women can be interpreted as`a talking platypus effect' (Abramson et al, 1977), or as re¯ecting expectancy violation (Jussim et al, 1987).…”
Section: Discussionmentioning
confidence: 90%
“…This ®nding was somewhat unexpected, as it indicated signi®cantly higher Overall Performance for the women in all but the skewed units. Evidence of a pro-female bias in situations where (based on stereotypical assumptions) a pro-male bias was anticipated is occasionally found both in laboratory (Bigoness, 1976;Hamner et al, 1974;Jacobson and Effertz, 1974;Kryger and Shikiar, 1978;Pazy, 1992;Woehr and Roch, 1996) and in ®eld studies (Mobley, 1982;Peters et al, 1984;Powell and Butter®eld, 1994). The tendency to in¯ateÐrather than devalueÐthe assessment of women can be interpreted as`a talking platypus effect' (Abramson et al, 1977), or as re¯ecting expectancy violation (Jussim et al, 1987).…”
Section: Discussionmentioning
confidence: 90%
“…Two studies of actual employees in actual organizational settings find evidence of this phenomenon. Although there is evidence in the literature which suggests that, at least in certain situations, women can receive higher performance evaluations than men (see e.g., Peters et al, 1984) there is also evidence to indicate that success for men will tend to be attributed to competence while success for women will tend to be attributed to luck (see Etaugh & Brown, 1975;Wiener et al, 1971).…”
mentioning
confidence: 99%
“…This argument is rooted in social identity theory and builds on the idea that because raters are more familiar with their in-group, evaluations of out-group members are more susceptible to stereotyping (Oakes and Turner, 1986;Taylor, 1981). Studies that have examined this specific rater sex by ratee sex interaction have found only limited support (Davison and Burke, 2000;Peters et al, 1984). Elvira and Town (2001), however, indicate that a similar interaction effect with regard to supervisor and subordinate race was present in their sample data.…”
Section: Research Hypothesesmentioning
confidence: 47%
“…While there is substantial research on gender bias in evaluation settings (Maurer and Taylor, 1994;Peters et al, 1984;Robbins and Denisi, 1993;Terborg and Shingledecker, 1983;Wexley and Pulakos, 1982), no prior study directly investigated whether expectations of bias do indeed cause women to prefer more objective evaluation styles, or whether men and women have different preferences regarding the level of evaluator discretion in appraisal settings. Yet, these questions are highly relevant to organizations and policy makers that are trying to create equal career opportunities for men and women, and to break through the glass ceiling (Bell et al, 2002;Blau and Kahn, 2006;Dreher, 2003).…”
Section: Introductionmentioning
confidence: 97%